Effects of Aluminium Toxicity on Early Growth and Nodulation of Groundnut in Solution Culture - Kasran, Rosmin (1989)
Five glasshouse experiIrents were undertaken using groundnut (Arachis hypogaea L. cv. Mat jam) plants grown in nutrient solution under acid conditions. The minimum total external solution concentrations of phosphorus, calcium and magnesium required for optimum non- syimbiotic growth of groundnut by the depleting nutrient method in 5 L pots at pH 4.75 ± 0.1 for 40 days'Were 200, 400 and 100 pM, respectively. This corresponds to their nutrient concentrations in youngest fully expanded leaves (YFEL) of 0.33, 1.47 and 0.32%. The H+ ion concentration at pH 3.5 did not affect plant top dry 'Weight but markedly decreased root growth and. length. The pH level recommended for growth of groundnut was 4.4. The non-toxic concentration of aluminium for growth of tops and root elongation in groundnut supplied with 400 pM ca was < 12.2.